Desain Pembelajaran Keagamaan Islam Berbasis Neurosains - Saifurrahman Saifurrahman (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2019)
Learning is a stimulation for the development of thinking, but often learning is not designed according to the science of thinking or neuroscience. This article offers a fresh idea of how Islamic religious learning design is designed based on neuroscience. This study uses library research with a descriptive analytical approach to the themes of Neuroscience that can be applied in elementary school education and the results of the discussion of this article show that the design of Islamic religious learning can at least be done with three schemes; opening (fluorescent lighting, thought beats, challenging class settings etc.); Inti (sink setting/ ambak, expository, discussion, role play and assessment); Cover (enker and the like)